The Brahmo Samaj and the shaping of the modern Indian mind - Kopf, David (Princeton legacy library., 1979)
As the forerunners of Indian modernization, the community of Bengali intellectuals known as the Brahmo Samaj played a crucial role in the genesis and development of every major religious, social, and political movement in India from 1820 to 1930. David Kopf launches a comprehensive generation- to-generation study of this group in order to understand the ideological foundations of the modern Indian mind. His book constitutes not only a biographical and a sociological study of the Brahmo Samaj, but also an intellectual history of modern India that ranges from the Unitarian social gospel of Ramm.